2020
DOI: 10.1177/0272431620940386
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Compensatory Parental Responses to Peer Victimization

Abstract: Scientific evidence for effective parental responses to peer victimization (PRPV) is sorely lacking. In this conceptual article, we first consider direct parental efforts to reduce peer victimization (i.e., direct PRPV) through explicitly coaching children about how to cope with peer victimization or intervening in the situation. We encourage researchers to examine whether and how direct PRPV may be successful, acknowledge possible limitations, and explore other forms of parental influence in the context of pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…Parental advice to be assertive predicted higher peer victimization over time, yet other forms of parental advice did not predict peer victimization experiences. Thus, in a pattern similar to Troop-Gordon et al's (2020) results concerning early adolescents' expectations of teachers, active parental responses predicted engaged coping strategies, whereas passive parental responses predicted disengaged coping strategies. The implications of parental responses for early adolescents' peer victimization experiences were less clear and thus require further investigation.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Parental advice to be assertive predicted higher peer victimization over time, yet other forms of parental advice did not predict peer victimization experiences. Thus, in a pattern similar to Troop-Gordon et al's (2020) results concerning early adolescents' expectations of teachers, active parental responses predicted engaged coping strategies, whereas passive parental responses predicted disengaged coping strategies. The implications of parental responses for early adolescents' peer victimization experiences were less clear and thus require further investigation.…”
supporting
confidence: 72%
“…Following these results, in a conceptual contribution (Erath, Pettit, & Troop-Gordon, 2020), we contrast parental efforts to reduce peer victimization directly (e.g., contact school, provide behavioral advice to adolescent) with compensatory parental responses to peer victimization. Compensatory responses occur when parents intentionally step up their actions-above and beyond their usual parenting-in an explicit effort to support the psychological health of children who experience peer victimization, independent of efforts to reduce peer victimization directly.…”
mentioning
confidence: 99%
“…Specifically, stakeholders (e.g., parents, schools, and policymakers) should not only build facilitative environments by enhancing PI and reducing PV, but they also need to decrease CFC-I and nurture CFC-F in young people. Of note, peers become a more important source than parents in affecting adolescents' daily lives although parents are still crucial for big decisions and comfort when needed ( Buist, Deković, Meeus, & van Aken, 2004 ; Erath, Pettit, & Troop-Gordon, 2021 ). The significant interaction between PI and PV on adolescent CFC suggests the importance of facilitating both the family and peer systems simultaneously to strengthen adolescents' positive future orientation.…”
Section: Discussionmentioning
confidence: 99%
“…Dyads additionally reported that mothers engaged in behavior that did not directly address the peer victimization but served emotion-focused coping goals. While such compensatory behaviors have been theorized previously (Erath et al, 2021), this is one of the first studies, to date, to document their use. Compensatory behaviors may reflect a subtle uptick in established parenting patterns, such as providing a supportive environment for their child.…”
Section: Compensatory Behaviorsmentioning
confidence: 81%